(untitled) (Scientia Agropecuaria, 2012)
A new procedure has been used to separate and quantify the free radical-scavenging activity of individual compounds 18 samples of Thymus vulgaris and 12 samples of Rosmarinus officinalis (both used as natural food preservatives), based on the combination of HPTLC (High Performance Thin Layer Chromatography) and postchromatographic DPPH● radical derivatization. The compounds thymol and rosmarinic acid in T. vulgaris and R. officinalis, respectively, were identified by comparisons of their Rf values and UV spectra to standards analyzed under identical analytical conditions, while the quantitative data were calculated from their calibration curves. We found that not only that the biomass yield but also the metabolite content in herbs, depend on the ecotype (genetics) and on the agro ecological conditions. The effect of the ambient on the metabolite content is extremely significant and also on their antioxidant activity (One-way ANOVA with Newman-Keuls Multiple Comparison post test was performed using GraphPad Prism version 4.00 for Windows, GraphPad Software). This work pretends to demonstrate the great importance of using new technologies for the selection of the best materials used as natural food preservatives.